Energetics of walking and running - Sprott, J. C.
What follows is an estimate of the power consumed in walking and in running as a function of a person's mass (m), leg length (L), and running speed (v). The speed at which running becomes more efficient than walking is calculated. An estimate is given for the maximum sustained running speed. The minimum required coefficient of friction is calculated for walking and running.